Feminization and masculinization facial surgeries: forensic repercussions (Research, Society and Development, 2021)
Individuals who are characterized by strong and persistent identification with the opposite sex (gender dysphoria) often seek plastic surgeons for sex reassignment and/or to accentuate gender-specific facial features, surgically modifying facial features, wishing to be accepted in society as part of antagonistic sex. Surgical procedures aimed at modifying and reconstructing facial bone characteristics, as well as soft tissues, are being performed to make the face of trans women more feminine (facial feminization surgery) and trans men more masculine (facial masculinization). These procedures may have forensic consequences, due to difficulties in estimating the sex, with regard to the possible need for recognition of the individual through Forensic Facial Reconstruction, and consequently, in identifying people who have undergone this type of surgery. Such consequences, although important, are little considered in scientific studies. Thus, this study brings a theoretical and reflective approach to forensic aspects and considerations in human recognition and identification of transsexual individuals who underwent feminization to masculinization facial surgeries.